2016
DOI: 10.1002/jctb.4931
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of struvite recovery from wastewater and reusing for heavy metals immobilization in contaminated soil

Abstract: BACKROUND Few studies have been carried out to connect nutrients recovery from wastewater and heavy metals immobilization in contaminated soil. To achieve the goal, ammonia nitrogen (AN) and phosphorus (P) were recovered from rare‐earth wastewater by using the formation of struvite, which was used as the amendment with plant ash for copper, lead and chromium immobilization. RESULTS AN removal efficiency and residual P reached 95.32 ± 0.73% and 6.14 ± 1.72 mg L−1 under optimal conditions: pH=9.0, n(Mg): n(N): n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 51 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…The pH solution (8, 9 and 10) was adjusted by injection of 1 N KOH from the bottom mixed with air. The estimated retention time within the reactor was to be 13,17,20,25,31 minutes, while the reaction temperature was fixed at 30 O C. In this study, pH was observed every 5-min intervals. Then the crystalline solid was formed in the bottom of the reactor, whereas the liquid left from the conical part of the reactor owing to an overflow system.…”
Section: Mathematical Modeling Of Rsm Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH solution (8, 9 and 10) was adjusted by injection of 1 N KOH from the bottom mixed with air. The estimated retention time within the reactor was to be 13,17,20,25,31 minutes, while the reaction temperature was fixed at 30 O C. In this study, pH was observed every 5-min intervals. Then the crystalline solid was formed in the bottom of the reactor, whereas the liquid left from the conical part of the reactor owing to an overflow system.…”
Section: Mathematical Modeling Of Rsm Methodsmentioning
confidence: 99%
“…Here, the change of reaction crystallization in the recovery of struvite due to the presence of calcium ions has been demonstrated in a batch crystallizer 13 and in a continuous crystallizer 14,15 . Correspondingly, reaction crystallization of struvite for recovery of phosphate ions from wastewaters is a complex technological challenge 16,17,18 . This requires fully controlled conditions for struvite production and partly purifying wastewater systems 17 , while desirable amounts of precipitated struvite can be recovered by typically control of the precipitating process in the reactor system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illite is a layered silicate mineral with high cation exchange capacity and specific surface area and strong adsorption capacity of heavy metals [14,15]. Struvite contains N, P, Mg and other nutrients needed by plants [16], and it has the potential to stabilise heavy metals in soil [17]. Pyroxene is a silicate mineral produced by reaction of CaO, MgO and SiO 2 at high temperature [18].…”
Section: Xrd Analysis For Saline-alkali Soilmentioning
confidence: 99%
“…The saturation index (SI) was calculated according to Eqn (1): 27,28 where log IAP is the logarithm of the ion activity product calculated from the stoichiometry; Ks is the temperature-corrected thermodynamic solubility product; and SR is the supersaturation ratio. A SI greater than zero indicates that the solution is supersaturated, and a SI value 0 indicates the solution is in equilibrium or undersaturated.…”
Section: Calculations Of the Saturation Indexmentioning
confidence: 99%